The Role of Microglia/Macrophages Activation and TLR4/NF-κB/MAPK Pathway in Distraction Spinal Cord Injury-Induced Inflammation - Liang, Weishi; Han, Bo; Hai, Yong; Liu, Yuzeng; Liu, Xing; Yang, Jincai; Sun, Duan; Yin, Peng (Frontiers in Cellular Neuroscience, 2022)
Distraction spinal cord injuries (DSCIs) often occur as the neurological complication of distraction forces following the implantation of internal fixation devices during scoliosis correction surgery. However, the underlying mechanism behind these injuries remains unclear. The present study aimed to explore the activation of microglia and macrophages, as well as changes in TLR4-mediated NF-κB and MAPK pathway activity after DSCIs in Bama miniature pigs. Prior to surgical intervention, the pigs were randomly divided into three groups: the sham group, the complete distraction spinal cord injury (CDSCI) group, and the incomplete distraction spinal cord injury (IDSCI) group. After surgery, the Tarlov and individual limb motor scale (ILMS) scores were used to evaluate changes in the pigs’ behavior. All pigs were euthanized seven days after surgery, and histopathological examinations of the spinal cord tissues were performed. Immunohistochemistry was used to detect Caspase-3 expression in the anterior horn of spinal gray matter tissues. Immunofluorescence staining was utilized to assess the M1/M2 phenotype changes in microglia/macrophages and NF-κB P65 expression in central DSCI lesions, while western blotting was performed to determine the expression of TLR4/NF-κB/MAPK pathway-related proteins. The results of the present study showed that the Tarlov and ILMS scores decreased significantly in the two DSCI groups compared with the sham group. HE and Nissl staining revealed that the tissue structure and nerve fiber tracts in the distracted spinal cord tissues were destroyed. Both DSCI groups showed the number of survived neurons decreased and the Caspase-3 expression increased. The results of the immunofluorescence staining indicated that the CD16 and CD206 expression in the microglia/macrophages increased. Between the two DSCI groups, the CDSCI group showed increased CD16 and decreased CD206 expression levels. The intensity of the fluorescence of NF-κB P65 was found to be significantly enhanced in pigs with DSCIs. Moreover, western blot results revealed that the expression of TLR4, p-IκBα, NF-κB P65, p-JNK, p-ERK and p-P38 proteins increased in spinal cord tissues following DSCI. The present study was based on a porcine DSCI model that closely mimicked clinical DSCIs while clarifying DSCI-associated neuroinflammation mechanisms, in turn providing evidence for identifying potential anti-inflammatory targets.